Cannabis use and violence in patients with severe mental illnesses: A meta-analytical investigation. (April 2019) - Dellazizzo, Laura; Potvin, Stéphane; Beaudoin, Mélissa; Luigi, Mimosa; Dou, Bo Yi; Giguère, Charles-Édouard; Dumais, Alexandre
Highlights: Findings showed a moderate cannabis-violence association in severe mental illness. The association was higher for cannabis misuse in comparison to cannabis use. Cannabis use should be considered in violence risk prevention and management. Abstract: Background: The relationship between cannabis and violence remains unclear, especially amid those with severe mental illnesses (SMI). The objective of this meta-analysis was to investigate the cannabis-violence association in a population of individuals with a SMI. Method: A systematic search of literature using PubMed, PsychINFO, Web of Science and Google scholar was performed (any time-August 2018). All peer-reviewed publications assessing both cannabis use and the perpetration of violence in an SMI sample were included. Data on several key study characteristics such as the proportion of SMI in the sample as well as the number of cannabis users and violent participants were extracted. Odds ratios (OR) were likewise extracted and aggregated with random-effects models. Results: Of the potential 2449 articles that were screened for eligibility, 12 studies were analyzed using a random-effect meta-analysis. Results showed a moderate association between cannabis use and violence (OR = 3.02, CI = 2.01–4.54, p  = 0.0001). The association was significantly higher when comparing cannabis misuse (OR = 5.8, CI = 3.27–10.28, p  = 0.0001) to cannabis use (OR = 2.04, CI = 1.36–3.05, p  = 0.001). Conclusion: These findings are clinically relevant for violence prevention/management and highlight the necessity of further investigations with methodologically-sound studies. Thus, longitudinal studies adjusting for important confounding factors (i.e., psychopathic traits and stimulant use) are warranted.